Arduino-enhanced smart hat for blind navigation - Sharom, Faez Ashraf; Che Kar, Siti Aishah; Ismail, Syila Izawana; Abdullah, Rina; Ahmed, Norizan; Mohamed, Syazilawati (Faculty of Pharmacy, 2025)
Arduino-Enhanced Smart Hat for Blind Navigation is an innovative wearable technology designed to improve mobility and safety for the visually impaired. Utilising an Arduino Uno, the system integrates ultrasonic sensors, a buzzer, and vibration motors, all embedded seamlessly into a comfortable hat. The ultrasonic sensors continuously scan the environment for obstacles, calculating distance with precision. When an obstacle is detected within a predefined range, the system triggers tactile feedback through a gentle vibration and an optional audible alert via a buzzer. This dual-sensory warning system allows users to navigate their surroundings with enhanced awareness, promoting greater independence and confidence in unfamiliar environments. The Guardian Hat is a practical, cost-effective solution that provides real-time, hands-free obstacle detection. By offering both vibration and sound alerts, it caters to diverse user needs, making it adaptable to varying levels of sensory perception. The simplicity, affordability, and user-centric design of the system make it a highly effective tool in improving the quality of life for the visually impaired, fostering autonomy and ensuring safety in daily navigation.